Emerging Challenges in Filovirus Infections - Ikwaras Okware, Samuel (IntechOpen, 2020)
This book discusses the emerging challenges of the filovirus infections Ebola and Marburg virus disease. It reviews the complex ecology and role played by bats and other suspected intermediate hosts, including pigs. Also examined are the challenges for other modes of transmission and early diagnosis and detection. The immunology and pathogenesis of the infections and the impact on the host?s immune systems are discussed. The rare occurrence of Marburg virus infection in pregnancy and the long-term consequences of sexual transmission by survivors is further examined. These discussions have the potential to support future management of outbreaks and guide research for vaccines and medication for Ebola and Marburg disease.